ADOPSI SISTEM JAJAR LEGOWO PADA USAHATANI JAGUNG: FAKTOR PENENTU DAN IMPLIKASINYA TERHADAP PENDAPATAN PETANI - Endang Lastinawati; Tiara Priscilia Putri Henta Tjika; Windi Lestari; Septianita; Chuzaimah (Jurnal AGRIBIS, 2026)
This study aims to analyze the factors influencing corn farmers' decisions to adopt the Jajar Legowo planting system and to compare the income levels between adopters and conventional farmers in Gemiung Village, Buana Pemaca District, South OKU Regency. The research method employed a survey with proportional stratified simple random sampling of 42 respondents. Data were analyzed using the Logistic Regression Model (Logit) and the Independent Sample t-Test. The regression results indicated that land area, education, and income significantly influenced farmers' adoption decisions (Sig < 0.05) with a Nagelkerke R Square value of 0.880. A unique finding showed that land area had a negative effect, suggesting that intensification is more preferred by small-scale farmers. Economically, the Jajar Legowo system yielded higher production (19,200 kg) compared to the conventional system (16,882 kg). This resulted in a net income of IDR 63,632,330 for the Jajar Legowo system, which was significantly higher than the conventional system's income of IDR 52,194,648 (p < 0.05). The economic efficiency of Jajar Legowo was also superior, with an R/C ratio of 2.97. This study recommends the need for intensive technical assistance for large-scale farmers to promote equitable technology adoption.